Semi-automatic segmentation using MR images I. - Seah, Chiao Luan. (2009)
Magnetic resonance imaging (MRI) is becoming clinically important in the assessment of joint injury and osteoarthritis because of its excellent soft tissue contrast. Segmentation of specific tissue structures is beneficial to the diagnosis and treatment of pathologies. A semi-automatic segmentation code based on a combination of histogrambased techniques, morphological operations and an active contour method was proposed to delineate the meniscus from knee MR images. The objective of the project is to achieve a fast and accurate segmentation of the meniscus.